Pengaruh Harga, Promosi, dan Kualitas Layanan terhadap Penjualan Layanan Telekomunikasi PT Sinergi Inti Andalan Prima Tbk di Meruya Ilir - Nabila Nasyahta Bunawan; Yugi Setyarko (Global Leadership Organizational Research in Management, 2025)
This study aims to examine the influence of pricing, promotion, and service quality improvement on the sales level in the telecommunications services of PT Sinergi Inti Andalan Prima, Tbk, located in Meruya Ilir, West Jakarta. The research adopts a quantitative approach using primary data obtained through the distribution of structured questionnaires. The population in this study consists of all permanent employees of the company, totaling 35 individuals. Given the relatively small population, a saturated sampling technique was applied, making all members of the population the research sample. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. The analysis process involved validity and reliability testing, classical assumption testing, and hypothesis testing through multiple linear regression analysis to determine the effect of each independent variable—pricing, promotion, and service quality improvement—on the dependent variable, sales level. The findings reveal that pricing has a significant positive effect on the sales level, indicating that appropriate and competitive pricing strategies can enhance sales performance. Similarly, service quality improvement also shows a significant positive influence on sales level, suggesting that better service delivery directly contributes to increased customer satisfaction and sales outcomes. Conversely, the study finds that promotion does not have a significant effect on sales level in this case. This may be due to promotional activities not being optimally targeted, lacking sufficient frequency, or failing to deliver persuasive messages to the intended market segment. Overall, the results highlight the importance of focusing on competitive pricing strategies and continuous improvement in service quality as key drivers of sales growth in the telecommunications sector. The study recommends that PT Sinergi Inti Andalan Prima, Tbk prioritize these two aspects while reevaluating its promotional strategies to ensure better alignment with customer needs and market conditions.